Jaw region endometriosis: case report: Endometriosis de región mandibular: reporte de caso - Contreras Gala, Katherine L. (2021)
Introduction: Endometriosis is a chronic gynecological disease, which refers to the presence of endometrial glands and stroma outside the uterine endometrium. This entity has a frequency of 10 to 15% in women of reproductive age, and its most common site of presentation is the ovary. At the extrapelvic level, the most common location is the gastrointestinal and genitourinary location. However, it can occur in any location. Presentation: The case of a 40-year-old female patient with a face tumor in the mandibular region is described, presenting with a disease time of 2 years. Among the important antecedents, two months before the appearance of the tumor region, the patient underwent endodontic surgery of a lower molar tooth, contiguous to the mandibular. Likewise, one month before the appearance of the tumor, the patient underwent an exploratory laparoscopy for electrofulguration of endometriotic foci in the uterine myometrium. The patient underwent a surgical resection of the tumor in the mandibular region described; and after reviewing the histological and immunohistochemical slides at the institution, the diagnosis of endometriosis was established. Conclusion: Extrapelvic endometriosis is rare in our country, and its diagnosis requires experience and visual training in the recognition of normal endometrial tissue. The presentation of this case was considered important because it would be the first case reported in Peru and in the world, of an endometriosis located in the mandibular region.